Loss of macroH2A1 decreases mitochondrial metabolism and reduces the aggressiveness of uveal melanoma cells - Giallongo, Sebastiano; Di Rosa, Michelino; Caltabiano, Rosario; Longhitano, Lucia; Reibaldi, Michele; Distefano, Alfio; Lo Re, Oriana; Amorini, Angela Maria; Puzzo, Lidia; Salvatorelli, Lucia; Palmucci, Stefano; Tibullo, Daniele; et al. (Aging, 2020)
Uveal melanoma (UM) is the most common primary intraocular tumour in adults. The most accurate prognostic factor of UM is classification by gene expression profiling. Currently, the role of epigenetics is much less defined compared to genetic mechanisms. We recently showed a strong prognostic role of the expression levels of histone variant macroH2A1 in UM patients. Here, we assessed the mechanistic effects of macroH2A1 on UM progression.UM cell lines were stably knocked down (KD) for macroH2A1, and proliferation and colony formation capacity were evaluated. Mitochondrial function was assayed through qPCR and HPLC analyses. Correlation between mitochondrial gene expression and cancer aggressiveness was studied using a bioinformatics approach.MacroH2A1 loss significantly attenuated UM cells proliferation and aggressiveness. Furthermore, genes involved in oxidative phosphorylation displayed a decreased expression in KD cells. Consistently, macroH2A1 loss resulted also in a significant decrease of mitochondrial transcription factor A (TFAM) expression, suggesting impaired mitochondrial replication. Bioinformatics analyses uncovered that the expression of genes involved in mitochondrial metabolism correlates with macroH2A1 and with cancer aggressiveness in UM patients. Altogether, our results suggest that macroH2A1 controls UM cells progression and it may represent a molecular target to develop new pharmacological strategies for UM treatment.
Keywords: histony; Gene Expression Regulation, Neoplastic; nádory uvey; Mitochondria; Neoplastic Stem Cells; Cell Line, Tumor; Uveal Melanoma; Cell Proliferation; epigenetics; histones; uveální melanom; regulace genové exprese u nádorů; uveal melanoma; macroH2A1; Uveal Neoplasms; DNA vazebné proteiny; mitochondriální proteiny; melanocyty; Melanoma; Mitochondrial Proteins; lidé; Transcription Factors; transkripční faktory; Humans; proliferace buněk; Melanocytes; Histones; nádorové kmenové buňky; nádorové buněčné linie; melanom; DNA-Binding Proteins; mitochondrie; metabolism